Dropout stories of Andalusian university students - Gijón, José; Gijón, Meriem K.; García, Pablo; Lizarte, Emilio J. (Frontiers in Education, 2023)
The abandonment of university studies is a problem that affects the balance and correct organization of university systems throughout the world and that has undesirable personal consequences in advanced societies. Dropping out of school has a multidimensional explanation. Among the causes, associated with each other, that originate it, the following factors stand out: psychological, social, economic, psycho-pedagogical, institutional, and didactic. Studying how all these dimensions act and relate to each other in specific cases of people who drop out of Higher Education, helps us to better understand the phenomenon and to develop prevention measures in university institutions. This text presents the results of biographical-narrative research carried out among the student population in a situation of abandonment of the universities of Andalusia that has allowed us to recover 22 stories of abandonment carried out by as many ex-students who were enrolled in any of the nine universities. Andalusians publish in any of the different university degree studies. The biographical texts have been subjected to narrative analysis to achieve personal exemplifications and characterize paradigmatic cases of relationship between the dimensions of the problem, using concept mapping to present the outcomes.